Valuing public and private urban tree canopy cover1. (10th December 2013) - Pandit, Ram; Polyakov, Maksym; Sadler, Rohan
<x xml:space="preserve">Abstract</x> In this paper, we estimate the effect of tree canopy cover on sales price of urban residential properties in Perth, Western Australia. Using a data set of 5606 single family homes sold in 2009 and a spatial hedonic model with three spatial effects – spatial‐temporal lag on dependent variable, spatial error, and spatially lagged independent variables – we estimated the location‐specific effect of tree canopy cover. Tree canopy cover increases the property value when located on adjacent public space, but decreases the value when it is on own property and on the adjacent property within 20 m of property boundary. The results are suggestive that council urban tree planting programs provide significant private benefits to homeowners.